CYANOPROCARIOTES AND ALGAE OF FIELDS PLANTED WITH COTTON - Tursunova Shaxodatxon Abdujaborovna; Maxsudova Ruhshonaxon Barkamoljon qizi (Galaxy International Interdisciplinary Research Journal, 2023)
Soil fertility is one of the pressing issues of today. This article presents the types and derivatives of soil algae, their Systematics, determined from the soils of fields where acorns are planted. Activities such as the conduct of agrotechnical activities on field soils planted with Acorns, the implementation of irrigation, the feeding of acorns with mineral fertilizers caused the development of algoflora on these soils.